Design expert software assisted development and evaluation of empagliflozin and sitagliptin combination tablet with improved in-vivo anti-diabetic activities. Issue 3 (March 2023) - Hossain, Md Saddam; Jahan, Sadia; Al Rezwan Rahman, Sad; Rahman, Mashiur; Kumar, Diponkor; Paul, Susmita; Chandra Rajbangshi, Joy
Abstract: Background: The combination of empagliflozin and sitagliptin to treat type-2 diabetes might be more economical and patient compliance with an additive improvement in glycemic control due to complementary modes of action. Aim of the study: To design, formulate and optimize an immediate tablet dosage form containing empagliflozin and sitagliptin utilizing statistically reliable study design followed by in-vitro and in-vivo testing. Method: ology: To determine the effects of copovidone (X1) and croscarmellose sodium (X2) amounts on the dependent variables of disintegration time and percent drug release, the formulation was developed using Design Expert Software v.13's direct compression method-based central composite design optimization study. The formulations' assay, dissolution, friability, hardness, weight variation, disintegration, and anti-diabetic effects were evaluated in comparison to the standard drug. The analysis included the use of high performance liquid chromatography (HPLC) assay methods. Mice were employed to investigate the efficacy of an anti-diabetic drug after they were administered a high-fat diet and two injections of streptozotocin at a dosage of 30 mg/kg BW each. Results: Formulation of F3 out of nine had all in-vitro parameters at the most satisfactory condition. It was found that assay of the best formulation is 100.99% and 100.19% for empagliflozin and sitagliptin respectively. The disintegration time of F3 was found at 5.32 min. Percentage release of empagliflozin in 30 min was found 89.05% while sitagliptin was with 93.76%. The results showed that administration of F3 significantly reduced FBG (68.61%, p < 0.0001), total cholesterol levels (70.29 ± 0.48; p < 0.0001), triglycerides (70.20 ± 0.40, p < 0.0001); HDL levels (52.50 ± 0.31; p < 0.0001), LDL levels (33.34 ± 0.28; p < 0.0001), compared to diabetic control, this effect was comparable to metformin treatment. Conclusion: The direct compression approach has been used to develop, and optimize a new combination tablet incorporating empagliflozin and sitagliptin with better dissolution rate and anti-diabetic action.